Serum metabolomics signature of maternally inherited diabetes and deafness by gas chromatography–time of flight mass spectrometry - Baige Cao; Huijuan Lu; Peng Liu; Yinan Zhang; Congrong Wang (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction The aim of this study was to identify a metabolic signature of MIDD as compared to healthy controls and other types of diabetes. Methods We performed a comprehensive serum metabolomic analysis using gas chromatography‐time of flight mass spectrometry (GC‐TOFMS) in participants diagnosed with MIDD (n = 14), latent autoimmune diabetes in adults (LADA) (n = 14), type 2 diabetes mellitus (n = 14), and healthy controls (n = 14). Each group was matched for gender and age. Results There were significant metabolic differences among MIDD and other diabetic and control groups. Compared with control, MIDD patients had high levels of carbohydrates (glucose, galactose, mannose, sorbose, and maltose), fatty acids (2‐Hydroxybutyric acid, eicosapentaenoic acid, and octadecanoic acid), and other metabolites (alanine, threonic acid, cholesterol, lactic acid, and gluconic acid), but low level of threonine. Compared with LADA, MIDD patients had high levels of threonic acid and some amino acids (alanine, tryptophan, histidine, proline, glutamine, and creatine) but low levels of serine. Compared with type 2 diabetes mellitus, MIDD patients had high levels of citrulline, creatine, 3‐Amino‐2‐piperidone, but low levels of ornithine, fatty acids (arachidonic acid and octadecanoic acid), and intermediates of the tricarboxylic acid cycle (malic acid and succinic acid). Conclusions Our study identified a specific metabolic profile related to glycolysis and the tricarboxylic acid cycle in MIDD that differs from healthy controls and other types of diabetes. This unique metabolic signature provides new perspectives for understanding the pathophysiology and underlying mechanisms of MIDD.